HEMOSPORIDOSIS OF FARM, DOMESTIC AND WILD ANIMALS ON THE TERRITORY OF RUSSIAN FEDERATION - N. A. Samoylovskaya; A. V. Uspensky; E. D. Novosad; E. A. Gulyukin; N. S. Malysheva; A. S. Buryonok; I. I. Orlova; I. N. Belousova (Российский паразитологический журнал, 2016)
Objective of research:  analysis of epizootic situation on protozoan blood parasitic diseases in domestic and wild animals on the territory of Russian Federation Materials and methods:  Veterinary reporting forms, sources of literature. Results and discussion:  The data on epizootic situation related to protozoan blood parasitic diseases in animals on the territory of  RF have been obtained and analyzed in this article. It was determined that for a proper evaluation of epizootic situation it is necessary to combine the activities of scientific-research institutes and veterinary services for the purpose of development of monitoring based on recommendations of the International Epizootic Bureau (IEB).